Effect of triclosan on anuran development and growth in a larval amphibian growth and development assay. Issue 10 (24th April 2017) - Fort, Douglas J.; Mathis, Michael B.; Pawlowski, Sascha; Wolf, Jeffrey C.; Peter, Robert; Champ, Samantha
Abstract: A larval amphibian growth and development assay was performed to evaluate the potential effects of environmentally‐relevant concentrations of triclosan (TCS) on amphibian development and growth. Xenopus laevis were exposed to TCS 0.0 (control), 6.3, 12.5 and 25.0 μg l –1 (estimated maximum tolerable concentration) until 10 weeks post‐metamorphosis. At median metamorphosis time (Nieuwkoop and Faber stage 62), five larvae per replicate were collected for snout–vent length, hind limb length and body weight measurements, and histopathological examination of thyroid glands. Endpoints evaluated at test termination were based on draft guidance (USEPA, 2010 ) and included: survival; snout–vent length; body weight; gender; nuptial pad development (males); and liver, kidney, gonad and gonadal ducts histopathology. Exposure to TCS did not decrease survival, induce general signs of toxicity, affect median metamorphosis time or alter sex ratios. Exposure to TCS 12.5 and 25 μg l –1 increased growth during the metamorphic stages relative to the control, but did not influence growth during the post‐metamorphic phase. Overall, several statistically significant findings were found in larvae exposed to TCS, such as a decrease in the prevalence of stage 3 Müllerian ducts in the anterior trunk sections of TCS 25.0 μg l –1 dose group females as compared to controls; most were not considered toxicologically relevant. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A larval amphibian growth and development assay was performed to evaluate the potential effects of environmentally‐relevant concentrations of triclosan (TCS) on amphibian development and growth at TCS 0.0 (control), 6.3, 12.5 and 25.0 μg l –1 (estimated maximum tolerable concentration). Exposure to TCS did not decrease survival, induce general signs of toxicity, affect median metamorphosis time or alter sex ratios. Exposure to TCS 12.5 and 25 μg l –1 increased growth during the metamorphic stages relative to the control, but did not influence growth during the post‐metamorphic phase.